The Use of ICT and Online Learning Applications during the COVID-19 Outbreak in Indonesia - Nurjaman, Asep; Sabilah, Fardini (Jurnal Pendidikan Progresif, 2022)
The use of ICT and online learning applications during the COVID-19 outbreak in Indonesia Objectives: This study aims to describe the impact of information and communication technology (ICT) and online learning applications on the quality of education during the covid-19 pandemic. Methods: The research was conducted in the college using a qualitative descriptive method. Data was collected through structured interviews, observation, and document analysis. Findings: The results showed that: first, the use of ICT and online applications in college increased during the pandemic; second, by using ICT and online learning applications, the teaching and learning process for lecturers and students become more independent, creative, flexible, and encourage students to increase their academic product; third, the academic products of lecturers and students experienced a significant increase. Conclusion: Understanding the magnitude of the impact of ICT on improving academic quality, can encourage the college to develop ICT.Keywords: covid-19 pandemic, university, ict, education qualityDOI: http://dx.doi.org/10.23960/jpp.v12.i2.202228